Abscisic acid and sucrose regulate tomato and strawberry fruit ripening through the abscisic acid‐stress‐ripening transcription factor. Issue 10 (4th May 2016) - Jia, Haifeng; Jiu, Songtao; Zhang, Cheng; Wang, Chen; Tariq, Pervaiz; Liu, Zhongjie; Wang, Baoju; Cui, Liwen; Fang, Jinggui
Summary: Although great progress has been made towards understanding the role of abscisic acid (ABA) and sucrose in fruit ripening, the mechanisms underlying the ABA and sucrose signalling pathways remain elusive. In this study, transcription factor ABA‐stress‐ripening (ASR), which is involved in the transduction of ABA and sucrose signalling pathways, was isolated and analysed in the nonclimacteric fruit, strawberry and the climacteric fruit, tomato. We have identified four ASR isoforms in tomato and one in strawberry. All ASR sequences contained the ABA stress‐ and ripening‐induced proteins and water‐deficit stress‐induced proteins (ABA/WDS) domain and all ASR transcripts showed increased expression during fruit development. The expression of the ASR gene was influenced not only by sucrose and ABA, but also by jasmonic acid (JA) and indole‐3‐acetic acid (IAA), and these four factors were correlated with each other during fruit development. ASR bound the hexose transporter ( HT ) promoter, which contained a sugar box that activated downstream gene expression. Overexpression of the ASR gene promoted fruit softening and ripening, whereas RNA interference delayed fruit ripening, as well as affected fruit physiological changes. Change in ASR gene expression influenced the expression of several ripening‐related genes such as CHS, CHI, F3H, DFR, ANS, UFGT, PG, PL, EXP1/2, XET16, Cel1/2 and PME . Taken together, this study may provide new evidence on the important role of ASR in cross‐signalling between ABA and sucrose to regulate tomato and strawberry fruit ripening. The findings of this study also provide new insights into the regulatory mechanism underlying fruit development.